Sports Injury: Rehabilitation Updates (Bangladesh Medical Journal, 2020)
Sports injuries occur as a result of physical activities carried out either for general recreational purposes or with more professional goals in mind. Sports injury can be defined as a pathologic process that adjourns training or competition and leads the athlete to seek medical treatment. Athletes of all levels suffer from injuries and experience a variety of acute and overuse syndrome that may range from minor to carrier-ending. The ever changing pattern of sports relevant injury, as well as limited available resource for rehabilitation in many areas of Bangladesh, is a matter of concern. Few sports clubs have some facilities; most of the athletes is often left to fend for himself. Key determinants of a successful sports injury rehabilitation program include the application of modern rehabilitation protocol under pertinent supervision, judicious application of  appropriate pharmaceutical agents and prompt surgical interventions when required. A Physiatrist would be the most logical choice to lead the rehabilitation team, holistic approach to injuries with conservative manner, proper guidance of physiotherapist and referring complicated injuries to the most appropriate specialist in a timely manner. Worldwide practiced rehabilitation protocols are sports injury based but this need to be developed according to the nature of injuries as well as available resources. The main focus are safe return to sports and minimizing re-injury on return to sport; this involves application of rehabilitation intervention in acute and chronic phases of injury. A key factor in all sports injury rehabilitation protocols is injury prevention; this involves data maintenance by teams or trainers, which is still not yet developed completely in Bangladesh. This review is an endeavor to elucidate some issues that are important and routinely practiced world-wide, with the aim to improve sports injury rehabilitation protocol for the developing world.Bangladesh Med J. 2020 May; 49(2) : 34-40